Design of Village, Community and Private Government Partnership Model in Labor: Study in Gempol Subdistrict, Pasuruan Regency - Khumaidi Khumaidi (Brawijaya University, 2019)
This research is focused on the implementation of partnerships which includes the legal basis of implementation, the role of each party, form and model of partnership. In fact, the employment partnership of the village government, the private sector and the community lasts quite a long time, but it has not been able to improve the quality of employment services. The results of the study show that employment partnerships are carried out by two parties, namely the village-private and public-private governments, which are based on the outcome of the agreement through an agreement, in the implementation there is no equality of position between the partners, the coordination relationship is low and there is no balance of benefits and risks. While the partnership form is similar to the build own operate, the partnership model is franchise and free market.